Interplay of human ABCC11 transporter gene variants with axillary skin microbiome functional genomics - Bruce R. Stevens; Luiz F. W. Roesch (Scientific Reports)
Abstract The human armpit microbiome is metabolically entangled with skin cell physiology. This “meta-organism” symbiotic mutualism results in sweat either with or without odor (osmidrosis), depending on host ABCC11 gene haplotypes. Apocrine metabolism produces odorless S-glutathione conjugate that is transferred by ABCC11 transporters into secretory vesicles, deglutamylated to S-Cys-Gly-3M3SH thiol, and exuded to skin surface. An anthropogenic clade of skin bacteria then takes up the thiol and bioconverts it to malodorous 3-methyl-3-sulfanylhexan-1-ol (3M3SH). We hypothesized a familial meta-organism association of human ABCC11 gene non-synonymous SNP rs17822931 interplaying with skin microbiome 3M3SH biosynthesis. Subjects were genotyped for ABCC11 SNPs, and their haplotypes were correlated with axilla microbiome DNA sequencing profiles and predicted metagenome functions. A multigeneration family pedigree revealed a Mendelian autosomal recessive pattern: the C allele of ABCC11 correlated with bacterial Cys-S-conjugate β-lyase (PatB) gene known for Staphylococcus hominis biosynthesis of 3M3SH from human precursor; PatB was rescinded in hosts with homozygous TT alleles encoding ABCC11 loss-of-function mutation. We posit that a C allele encoding functional ABCC11 is key to delivering host conjugate precursors that shape heritable skin niche conditions favorable to harboring Staphylococcus having genomics of odor thiol production. This provides existential insights into human evolution and global regional population ancestries.